2003
DOI: 10.1002/qua.10644
|View full text |Cite
|
Sign up to set email alerts
|

DFT study of the role of intermolecular interactions in the formation of stable halogeno– and ammineaqua– platinum(II) coordination compounds

Abstract: Density functional theory (DFT) and Hartree-Fock (HF) 2ϩ , the conditions for the formation of linear polynuclear complexes with PtOPt bonds (the so-called "platinum blues") are created.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…[1] According to recent quantum chemical calculations, the Pt-NH 3 bond in cisplatin is around 50 kJ mol -1 stronger than the Pt-Cl bond. [5] Nevertheless, it has been shown that the Pt II complex [Pt(NH 3 ) 3 Cl]Cl cannot easily be obtained in high yield as the direct reaction between cis-or trans-[Pt(NH 3 ) 2 Cl 2 ] and 1 mol-equiv. of NH 3 4 ]Cl 2 .…”
Section: Cis-[(nhmentioning
confidence: 98%
See 4 more Smart Citations
“…[1] According to recent quantum chemical calculations, the Pt-NH 3 bond in cisplatin is around 50 kJ mol -1 stronger than the Pt-Cl bond. [5] Nevertheless, it has been shown that the Pt II complex [Pt(NH 3 ) 3 Cl]Cl cannot easily be obtained in high yield as the direct reaction between cis-or trans-[Pt(NH 3 ) 2 Cl 2 ] and 1 mol-equiv. of NH 3 4 ]Cl 2 .…”
Section: Cis-[(nhmentioning
confidence: 98%
“…[(hppH) 2 NiCl 2 ] has already been synthesised by treating (hpp) 3 SiMe with NiCl 2 (py) 4 (py = pyridine) in toluene at room temperature and has been shown to feature a more or less tetrahedrally coordinated Ni atom. [15] Furthermore, the reaction between [PdCl 2 (cod)] (cod = cyclooctadiene) and hppH in CH 2 Cl 2 affords trans-[(hppH) 2 PdCl 2 ]. [16] Fast isomerisation seems to occur from a cis arrangement of the chlorido ligands to a more stable trans configuration during the course of the reaction such that it proved impossible to isolate the cis isomer.…”
Section: Cis-[(nhmentioning
confidence: 99%
See 3 more Smart Citations